Tail risk diversification strategy with flight-from-loss approach: Evidence from U.S. REITs - Koo, Kang Mo; Song, Jeongseop (International Journal of Strategic Property Management, 2025)
This study introduces a novel portfolio allocation strategy, the flight-from-loss approach, designed to diversify tail risk in the REIT market. The strategy reallocates capital toward assets that have historically outperformed during periods of extreme REIT losses, aiming to reduce downside risk and improve portfolio efficiency. Using U.S. REIT data from 1993 to 2023, we demonstrate that our portfolio approach reduces tail risk significantly, while also enhancing Sharpe ratios compared to a REIT-only benchmark portfolio. These diversification benefits are particularly significant during market crises, such as the subprime mortgage crisis, when risk reduction exceeds 30%. Our analysis further reveals that the minimum-variance and tangency portfolio approaches consistently outperform the equal-weight method in both risk control and performance efficiency. To test the strategy’s generalizability, we applied it to the Fama-French 30 industry portfolios, where the results of some industries indicate even stronger risk reduction and Sharpe ratio gains than in the REIT market. These findings suggest that the flight-from-loss strategy offers a practical, cross-sector solution for managing concentrated portfolio risks.